2018
DOI: 10.1002/csr.1501
|View full text |Cite
|
Sign up to set email alerts
|

The paradoxical nexus between corporate social responsibility and sustainable financial performance: Evidence from the international construction business

Abstract: The aim of the research is to substantiate the hypothesis of a paradoxical dynamic link between corporate social responsibility (CSR) and its material implications including sustainable corporate financial performance (CFP). By analysing a panel of 67 international construction companies from 2006 to 2015, we found that CSR programs can be detrimental to CFP in the short term but conducive to improving it in the long term.The findings of this research indicate that, in the international construction business, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 50 publications
6
60
0
Order By: Relevance
“…In another study, Nollet et al () suggested that although CSR practices have negative effect on economic business value in the short‐term, in the long run, it increases firms' economic business value. This result has been confirmed recently by Lu et al () who noted similar pattern in how CSR activities affect firms' financial performance. Using a meta‐analysis of 42 studies, Wang et al () showed that CSR leads to enhancement in financial performance of firms.…”
Section: Development Of Hypotheses and Conceptual Modelsupporting
confidence: 84%
See 1 more Smart Citation
“…In another study, Nollet et al () suggested that although CSR practices have negative effect on economic business value in the short‐term, in the long run, it increases firms' economic business value. This result has been confirmed recently by Lu et al () who noted similar pattern in how CSR activities affect firms' financial performance. Using a meta‐analysis of 42 studies, Wang et al () showed that CSR leads to enhancement in financial performance of firms.…”
Section: Development Of Hypotheses and Conceptual Modelsupporting
confidence: 84%
“…In fact, several prior research findings (Beiting, Ioannou, & Serafeim, 2015;Blasi, Caporin, & Fontini, 2018;Easy & Thanathavornlap, 2013;Ghoul, Guedhami, & Kim, 2017;Izzo, 2014;Lu, Ye, Chau, & Flanagan, 2018;Martínez-Ferrero et al, 2016;Nollet, Filis, & Mitrokostas, 2016;Wang, Dou, & Jia, 2016) suggest that CSR strategy can create economic value for a business in various ways. A study by Martínez-Ferrero et al (2016) that used international data indicated that investors and other stakeholders have a positive attitude towards CSR strategy.…”
Section: Csr Strategy and Economic Business Valuementioning
confidence: 99%
“…CSR research in the construction industry has accelerated in recent years; however, these studies are mainly focused on the development (Lou, Lee, & Mathison, 2011;Lu, Ye, Chau, & Flanagan, 2018;Watts, Dainty, & Fernie, 2015) and evaluation (Jones, Comfort, & Hillier, 2006;Petrovic-Lazarevic, 2008;Zhao, Zhao, Davidson, & Zuo, 2012) of CSR performance indicators. The construction industry is a typical project-based industry; hence, most of the CSR performance research is also project-based research.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of CSR on corporate financial performance is not immediate and unchanging, and it takes time to realize CSR for sustainable development (Lu et al, 2018). Lowest price bidding causes low profit or even loss and ultimately leads to insufficient resources for construction corporations to survive and perform CSR.…”
Section: Introductionmentioning
confidence: 99%
“…Construction by nature is socially responsible, making significant contributions to a nation's economy and creating many jobs (Alaghbari, Al‐Sakkaf, & Sultan, ). It helps to determine the nature, function, and appearance of construction products, such as buildings, roads, and bridges, all of which influence human health, economic activities, social behaviour, cultural identity, and civic pride (Lu, Ye, Chau, & Flanagan, ; Pearce, ). Based on which, Murray et al (, p. 9) emphasise that “it is the impact that the industry's products have on society's well‐being that provides the most compelling reasons for raising the profile of CSR.” However, construction is consistently alleged to be slow in embracing CSR (Lin, Ho, & Shen, ).…”
Section: The Context Of International Constructionmentioning
confidence: 99%